2011
DOI: 10.1007/s00181-011-0482-z
|View full text |Cite
|
Sign up to set email alerts
|

Convergence in income inequality? evidence from panel unit root tests with structural breaks

Abstract: This paper empirically tests whether there is evidence of convergence in income inequality, as predicted by several versions of the neoclassical growth model, using a large panel of annual data for the 48 contiguous states in the US over the 1916-2005 period. By implementing the panel LM unit root test developed by Im et al. (Oxford Bull Econ Stat 67:393-419, 2005, Panel LM unit-root tests with trend shifts, Mimeo, 2010) that allows for the presence of structural breaks and heterogeneity in the panel, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 47 publications
0
9
1
1
Order By: Relevance
“…Our results differ from those of Lin and Huang (2011) but agree with those of Bernard and Durlauf (1995) and Campbell and Mankiw (1989) when comparison is performed at the international level.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…Our results differ from those of Lin and Huang (2011) but agree with those of Bernard and Durlauf (1995) and Campbell and Mankiw (1989) when comparison is performed at the international level.…”
Section: Resultscontrasting
confidence: 64%
“…Panizza (2001) studied 48 contiguous states in the US and found inequality convergence. Similarly, a more recent study by Lin and Huang (2011) found overwhelming income inequality convergence in a large panel of annual data for 48 US states from 1916 to 2005. The results were obtained by implementing the panel LM unit root test, which allows for structural breaks and heterogeneity in the panel.…”
Section: Introductionmentioning
confidence: 88%
“…While the convergence analysis were implemented mainly in the field of economic growth and income, it is possible to say that empirical analyses on convergence of income for European countries began to appear in the late 1990s. Some of "uniformed" works are (Floyd & Shinew,1999;Apostolakis, 2003;Kutan & Yigit, 2004, 2005Narayan, 2007;Vojinovic et al, 2009;Oplotnik et al, 2011;Abbott et al, 2012;Lin & Huang, 2012). One can notice that these analyses vary substantially in their period of coverage, sample of countries, data and method, but authors generally agree that the new EU countries grew during the 1990s and 2000s in line with the neoclassical convergence hypothesis.…”
Section: Groups Of Analyzed Countries and Data Series Usedmentioning
confidence: 99%
“…Bu ülkelerdeki gelir dağılımı eşitsizliği artmış ve gittikçe birbirine benzer bir hal almıştır (Alvaredo ve Gasparini, 2015;Chambers ve Dhongde, 2016;Ravallion, 2003). Gelir dağılımının yakınsamasına ilişkin sınırlı sayıdaki çalışmalar genellikle ülke içi ve bölgeler arası eşitsizliğe odaklanmışlardır (Ezcurra ve Pascual, 2005, 2009Goerlich ve Mas, 2004;Gomes, 2007;Ho, 2015;Lin ve Huang, 2011, 2012a, 2012bMarina, 2000;Panizza, 2001;Tselios, 2009). Ülkeler arasındaki eşitsizliğin yakınsayacağına odaklanan çalışmalar ise birbirinden farklı ekonomik temellere sahip çeşitli ülke gruplarına odaklanmışlardır (Alvaredo ve Gasparini, 2015;Benabou, 1996;Bleaney ve Nishiyama, 2003;Chambers ve Dhongde, 2016Ravillion, 2003).…”
Section: Introductionunclassified